2015
DOI: 10.1002/ddr.21240
|View full text |Cite
|
Sign up to set email alerts
|

Dalbergia odorifera Extract Ameliorates UVB‐Induced Wrinkle Formation by Modulating Expression of Extracellular Matrix Proteins

Abstract: Preclinical Research Emerging evidence suggests that Dalbergia odorifera T. Chen (Leguminosae), an indigenous medicinal herb, has therapeutic potential. This study examined the antiwrinkle effects of ethanol extracts of D. odorifera in UVB-irradiated human skin cells. Ethanol extracts of D. odorifera and thier constituents, dalbergin and sativanone, induced expression of collagen type I and transforming growth factor (TGF)-β1 in human dermal fibroblasts. In HR-1 hairless mice exposed to UVB, the ethanol extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Wrinkles appear on the skin owing to the loss of elast dation of collagen in the dermis [33,34]. Many studies hav wrinkles increase and soluble collagen decreases in mouse amined whether M. amurensis branch extract affects collag sible for the antiwrinkle effect.…”
Section: Effect Of M Amurensis Branch Extract On Soluble Collagenmentioning
confidence: 99%
See 1 more Smart Citation
“…Wrinkles appear on the skin owing to the loss of elast dation of collagen in the dermis [33,34]. Many studies hav wrinkles increase and soluble collagen decreases in mouse amined whether M. amurensis branch extract affects collag sible for the antiwrinkle effect.…”
Section: Effect Of M Amurensis Branch Extract On Soluble Collagenmentioning
confidence: 99%
“…Wrinkles appear on the skin owing to the loss of elasticity resulting from the degradation of collagen in the dermis [33,34]. Many studies have been reported that with age, wrinkles increase and soluble collagen decreases in mouse and human skin [35].…”
Section: Effect Of M Amurensis Branch Extract On Soluble Collagen In ...mentioning
confidence: 99%
“…Studying herbal cosmetics for preventing skin photoaging, 40, 60, 80, or 100% ethanol extracts of Korean medicinal plant D. odorifera heartwood and their constituents sativanone (35) and dalbergin (53) exerted an increased expression of type I collagen in human dermal fibroblasts with increasing doses from 0.1 to 10 μ g/mL, especially in terms of 60% ethanol extract [ 52 ]. As a consequence, 60% ethanol extract was further assessed to examine the effects on the expression of other extracellular matrix (ECM) related proteins in human dermal fibroblasts, in which this and its constituents 35 (1 μ g/mL) and 53 (10 μ g/mL) elevated the levels of type I collagen, elastin, and transforming growth factor- β 1 (TGF- β 1) for 38 h treatment.…”
Section: Biological Activitiesmentioning
confidence: 99%